IMPROVING TEACHER COMPETENCE THROUGH TRAINING ON MAKING LEARNING MEDIA ASSISTED BY COREL DRAW - Sugiyem, Sugiyem; Tritanti, Asi (LPPM Univ. Ibn Khaldun Bogor, 2023)
Media in learning has a very important role because it can help optimize the learning process and facilitate students to understand the concepts taught. Along with the rapid development of science and technology, resulting in students' learning needs also changing. This requires teachers to always improve their knowledge and ability in developing learning media based on information and communication technology. This training aims to: increase the knowledge and skills of teachers in making learning media using the Corel Draw program that can be applied to help the teaching and learning process in the classroom. The result of this training activity was the increase in knowledge and skills of 12 teachers in making learning media using corel draw, this was evidenced by the completion of 10 learning media consisting of job sheets, handouts, and material exposure in the form of power points. Participant attendance during the training is 100% fulfilled. 85% of participants understood the theory presented by the team. Meanwhile, based on the results of practice, 83% of teachers can create learning media by utilizing the Corel Draw program. Based on mastery of the material, 78% of participants stated that they had no difficulty operating the Corel draw. The satisfaction level of trainees with an average score of 3.63 in the Very Satisfied category, and the usefulness of the training obtained an average score of 3.84 in the Very Useful category. This indicates that the training objectives can be achieved well